Design and Evaluation of the Antibacterial Peptide FK18: a Therapeutic Approach for Mastitis in Dairy Animals - Monteiro-Alfredo, Tamaeh; de O. Gutierrez, Camila; Almeida, Claudiane V.; da Silva, Vinicius C.; Gomes, Patrícia; de Oliveira, Caio F. R.; Madalozzo, Elisângela S.; Crusca, Edson [UNESP]; Orozco, Raquel M. Q.; Lima, Lucas; Cardoso, Marlon H.; Franco, Octávio L.; et al. (Springer Nature, 2025)
The rising prevalence of antimicrobial resistance (AMR) among microorganisms is a global health and economic concern with major implications for livestock, as traditional antibiotics lose efficacy and novel agents with distinct mechanisms of action are required. Mastitis, an inflammation of the mammary gland mainly caused by bacterial infections, affects dairy cows and sheep, impairing milk quality, reducing production, and generating economic losses. This study introduces FK18, a synthetic antimicrobial peptide (AMP) designed with bioinformatics tools, which showed potent antibacterial activity against mastitis-associated pathogens. Minimum inhibitory concentration (MIC) values were 5 µM for Staphylococcus aureus (bovine milk isolate) and 10 µM for Escherichia coli (ovine milk isolate). The antibacterial activity of FK18 was confirmed through multiple assays. Time-kill and membrane permeabilization studies demonstrated rapid bactericidal action, with near-complete reduction of CFU within 15 min for S. aureus and 120 min for E. coli (p < 0.05), which is consistent with disruption of the bacterial cell membrane. FK18 exhibited low toxicity toward eukaryotic cells, with an IC₅₀ of 21.46 µM in RAW 264.7 macrophages, and caused only 20% mortality in Galleria mellonella larvae at 100 µM. The peptide also remained stable under physiological saline conditions. Strong synergistic effects were observed with ciprofloxacin, with fractional inhibitory concentration index (FICI) values of 0.24 (S. aureus) and 0.01 (E. coli). By targeting bovine and ovine mastitis, this study highlights FK18 as a promising candidate to reduce antibiotic use in dairy animals and to support peptide-based therapeutic strategies in veterinary medicine.